Perioperative circulating tumor cell detection: Current perspectives. Issue 8 (2nd August 2016) - Kaifi, Jussuf T.; Li, Guangfu; Clawson, Gary; Kimchi, Eric T.; Staveley-O'Carroll, Kevin F.
ABSTRACT: Primary cancer resections and in selected cases surgical metastasectomies significantly improve survival, however many patients develop recurrences. Circulating tumor cells (CTCs) function as an independent marker that could be used in the prognostication of different cancers. Sampling of blood and bone marrow compartments during cancer resections is a unique opportunity to increase individual tumor cell capture efficiency. This review will address the diagnostic and therapeutic potentials of perioperative tumor isolation and highlight the focus of future studies on characterization of single disseminated cancer cells to identify targets for molecular therapy and immune escape mechanisms.